Mewujudkan Jemaat Cerdas Berdemokrasi Melalui Literasi Politik Berbasis Nilai Kekristenan Bagi Jemaat GBIS Kristus Gembala Alastuwo Karanganyar - Sarah Andrianti; Sri Wahyuni; Elisabet Widi Cahyaningsih; Thomas Prajnamitra; Memelianti Memelianti (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The involvement of church members in political life is a form of religious responsibility that must be rooted in Christian values. This community service activity was designed to enhance the political literacy of the GBIS Kristus Gembala Alastuwo Karanganyar congregation in preparation for the Simultaneous Regional Elections on November 27, 2024. Conducted over two sessions on November 3 and 10, 2024, the activity employed interactive discussions, lectures, and Biblical reflections that connect Christian values with political participation. Key themes included justice, honesty, servant leadership, and the rejection of money politics. The participants were also invited to reflect on the implementation of the regional elections held on December 8, 2024, as part of their learning process.The results show that the congregation's political awareness improved significantly. Members expressed a deeper understanding of the importance of electing trustworthy leaders who uphold integrity and public service. Furthermore, they demonstrated the courage to reject practices of money politics, indicating the internalization of Christian values in their civic decisions. By exploring democracy through the lens of faith, the congregation developed a more critical, wise, and responsible approach to voting. This initiative highlights the strategic role of the Church in shaping the political awareness of its members through ongoing political education grounded in Christian teachings. Continued efforts are essential to ensure that the congregation remains active in promoting moral leadership and societal transformation, beginning within the church community itself. Ultimately, churches can serve as centers for ethical political formation, equipping believers to contribute meaningfully to national development.